Serum zinc and copper levels: a marker of disease activity in senile cataract patients - Rai, Pooja S. K.; Deokar, Smita A.; Yadav, Ravi R.; Shelke, Sudarshan; Sundharan, Shimi (International Journal of Research in Medical Sciences, 2017)
Background: The present study was aimed to study alterations in levels of zinc and copper in senile cataract patients. Methods: 25 senile cataract patients in age group of 50 to 80 years and 25 control group were included in the study. Serum zinc and copper levels were determined by colorimetric method. Results: Significantly increased levels of serum zinc in cataract patients (199.8±24.32 µg/dl) were found as compared to controls (85.80±3.6 µg/dl) (p<0.0001). Serum copper concentration in cataract patients (249.5±34.59 µg/dl) were significantly (<0.0001) increased when compared to controls (125.7±4.66 µg/dl). Conclusions: Copper and zinc are involved in the pathogenesis of cataracts by different mechanisms such as damaging lipid membranes and lens capsule, crosslinking and in solubilization of lens proteins, leakage of beta and gamma crystalline into the aqueous humour through the production of hydroxyl radicals and peroxyl radicals. So, abnormal elevation of serum copper and zinc can be used as a marker in the opacification of the lens cortex in age-related human cataract.